Geographic structuring of the Plasmodium falciparum sarco(endo)plasmic reticulum Ca2+ ATPase (PfSERCA) gene diversity - Jambou, Ronan (2021)
Artemisinin, a thapsigargin-like sesquiterpene has been shown to inhibit the Plasmodium falciparum sarco/endoplasmic reticulum calcium-ATPase PfSERCA. To collect baseline pfserca sequence information before field deployment of Artemisinin-based Combination therapies that may select mutant parasites, we conducted a sequence analysis of 100 isolates from multiple sites in Africa, Asia and South America. Coding sequence diversity was large, with 29 mutated codons, including 32 SNPs (average of one SNP/115 bp), of which 19 were novel mutations. Most SNP detected in this study were clustered within a region in the cytosolic head of the protein. The PfSERCA functional domains were very well conserved, with non synonymous mutations located outside the functional domains, except for the S769N mutation associated in French Guiana with elevated IC 50 for artemether. The S769N mutation is located close to the hinge of the headpiece, which in other species modulates calcium affinity and in consequence efficacy of inhibitors, possibly linking calcium homeostasis to drug resistance. Genetic diversity was highest in Senegal, Brazil and French Guiana, and few mutations were identified in Asia. Population genetic analysis was conducted for a partial fragment of the gene encompassing nucleotide coordinates 87-2862 (unambiguous sequence available for 96 isolates). This supported a geographic clustering, with a separation between Old and New World samples and one dominant ancestral haplotype. Genetic drift alone cannot explain the observed polymorphism, suggesting that other evolutionary mechanisms are operating. One possible contributor could be the frequency of haemoglobinopathies that are associated with calcium dysregulation in the erythrocyte.